Extremely low frequency electromagnetic field generator suitable for plant in vitro studies - Prihatini R.; Abdullah M.P.; Bin Tuan Abdullah T.A.R.; Said I.; Hussin H.; Saleh N.M. (Czech Academy of Agricultural Sciences, 2023)
The extremely low frequency electromagnetic field (ELF-EMF) occurs naturally from the earth and artificially as a human invention. The objectives of this study were to develop a suitable ELF-EMF generator for in vitro plants culture studies and to determine the effect of ELF-EMF exposure on in vitro tobacco (Nicotiana tabacum) growth and chlorophyll content. An ELF-EMF generator, the coGEM 1, 000 was constructed using four coils of copper wires that were connected to a transformer, multimeter and rheostat. The coGEM 1, 000 suitable for tissue culture plants is able to produce stable and uniform 6 and 12 mT 50Hz ELF-EMF in the four coils of the ELF-EMF generator. The tobacco in vitro plantlets were exposed to 6 and 12 mT of 50 Hz ELF-EMF for a period of 0.5, 1, 2 and 4 hours. The exposure to 12 mT ELF-EMF for an hour increased plant growth (shoot height); whereas the exposure to 6 mT Elf-EMF for an hour increased chlorophyll a, chlorophyll b and the total chlorophyll content.